An historical perspective on the evolution of the United States internal revenue code from 1981-2001 - Johnson, Ryan A (Rhodes University, Faculty of Commerce, Department of Accounting, 2017)
The purpose of this study was to identify and analyse in an historical context the major changes to the United States' Internal Revenue Code during the period 1981-2001. This qualitative study relied on historical and legal interpretative approaches to better understand the political forces, personalities, and interactions that helped shape the legislative changes during this time period. The study focused on deep analysis of primary sources that best illuminated the latent narrative of four major tax actions: The Economic Recovery Tax Act of 1981, the Tax Reform Act of 1986, The Omnibus Budget Reconciliation Act of 1993, and The Economic Growth and Tax Relief Reconciliation Act of 2001. Archives, periodicals, and political rhetoric were examined in order to help shape the historical narrative. In addition, this study sought to identify major trends and paradigm shifts in the way United States tax policy was formed during the time period examined. The study identified several key trends that emerged in United States' tax policy during this period: the use of budget deficits as political tools; factors associated with accomplishing tax reform; gaps between political rhetoric of individual politicians and their political action; and the virtual disappearance of a political middle ground in United States budget politics. The study concluded by noting the economic and political significance of budget deficits and stressing the need for fundamental changes in voter responsibility in helping achieve lasting, broad-based tax reform and budgetary responsibility in the United States.
Keywords: United States -- Economic conditions -- 1981-2001; Income tax -- Law and legislation -- United States; Internal revenue law -- United States; Taxtion -- Law and legislation -- United States; United States. Economic Recovery Tax Act of 1981; United States. Tax Reform Act of 1986; United States. Omnibus Budget Reconciliation Act of 1993; United States. Economic Growth and Tax Relief Reconciliation Act of 2001